(untitled) (Research, Society and Development, 2022)
This article aims to demonstrate and understand the cognitive stimulation in the elderly, considering that the aging of the human being is a natural, gradual and continuous process. In view of the research carried out, it was possible to analyze that the theme "cognitive stimulation in the elderly" was known by most of the interviewees; however, they were unaware of the great importance of using such a method during treatment. Analyzing and addressing articles on the same theme, by other authors, it was concluded that the use of cognitive stimulation in the elderly brings autonomy, reasoning, and quality of life to the elderly, since this method stimulates brain functions such as attention, memory, perception, logical reasoning, sensation, and others.